2022
DOI: 10.3389/fnut.2022.1078281
|View full text |Cite
|
Sign up to set email alerts
|

Association of homocysteine and polymorphism of methylenetetrahydrofolate reductase with early-onset post stroke depression

Abstract: BackgroundHomocysteine (Hcy) has been indicated to be involved in pathophysiology of post stroke depression (PSD). There is a lack of research to study the relationship between Hcy metabolism genes and PSD. Our study aims to investigate the relationship among Hcy metabolism genes, Hcy, and early-onset PSD.Materials and methodsWe recruited 212 patients with stroke and collected their peripheral blood sample, clinical data, and laboratory test on admission. 12 single nucleotide polymorphisms (SNPs) in methylenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Consistent with our findings, Tang et al (2016) and J. Zhang et al (2022) reported that elevated serum levels of HCY at admission were related to depression 2 weeks and 6 months after the stroke onset. Through meta-analysis, Y. Chen et al ( 2022) also found that serum levels of HCY could be used as a biomarker for the prediction for the risk of early-onset PSD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our findings, Tang et al (2016) and J. Zhang et al (2022) reported that elevated serum levels of HCY at admission were related to depression 2 weeks and 6 months after the stroke onset. Through meta-analysis, Y. Chen et al ( 2022) also found that serum levels of HCY could be used as a biomarker for the prediction for the risk of early-onset PSD.…”
Section: Discussionsupporting
confidence: 91%
“…(2016) and J. Zhang et al. (2022) reported that elevated serum levels of HCY at admission were related to depression 2 weeks and 6 months after the stroke onset. Through meta‐analysis, Y. Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty papers included a total of 3714 stroke patients, 1560 with PSD and 2245 with non-PSD. [10,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Twenty papers had NOS scores of 4-9, 12 papers had ≥7, and the percentage of high-quality literature was 60%. The basic characteristics of the literature are shown in Table 1.…”
Section: Basic Informationmentioning
confidence: 99%